An Empirical Study on Choice of Law in China: A Home Run? - King Fung Tsang (Washington University Global Studies Law Review, 2022)
One of the most important issues in international commercial litigation is determining which country’s law governs the dispute. This choice-of-law question can be outcome determinative. Chinese courts have long been said to display a “homeward trend” in applying Chinese law, the lex fori, instead of foreign law in foreign-related civil litigations. Coined by Nussbaum in 1932, the term “homeward trend” refers to “a tendency to arrive, if possible, at the application of domestic law” in the courts’ judicial search for the applicable legal system. This homeward trend is frequently criticized by commentators, who regard it as a form of local protectionism. It damages the credibility of Chinese courts and erodes the confidence of foreign investors. In addition, it encourages forum shopping and causes unfairness to defendants. Critics believe that a modern choice-of-law system should allow parties to choose the law governing their relationship. When there is no such choice, courts should decide the case according to the law of the country with the closest connection to the transaction. These are known as the doctrines of party autonomy and closest connection respectively, and have been widely adopted by many countries, particularly in choice-of-law rules in contractual disputes. The homeward trend that sees Chinese courts applying lex fori indiscriminately is therefore contrary to these modern conflict doctrines. On the other hand, the homeward trend may have already faded in light of the choice-of-law reform more than a decade ago, with the promulgation of the Act on the Application of Laws over Foreign-related Civil Relationships (the “Choice of Law Act”) in 2010. The Choice of Law Act was touted as a “great achievement” and a “historic event,” indicating that “a socialist legal system with Chinese characteristics had been successfully achieved.” It certainly plays a key role in China’s modernization of its conflict of laws, particularly in regard to choice of law. With a renewed emphasis on modern choice-of-law doctrines such as party autonomy and closest connection, the choice-of-law rules therein are generally impartial. Particularly on the choice of law in contracts, where most conflict cases arise, the Choice of Law Act does not, on the surface, favor the application of Chinese law over foreign law. Further, since the One-Belt-One-Road initiative in 2013, the Supreme People’s Court (“SPC”) appears to have adopted a more open mind toward conflict-of-law matters. It is thus counterintuitive that the homeward trend, at least at any large scale, survives to this day. In addition, China’s increasing volumes of international trade suggest that it is in its national interest to adopt a modern choice-of-law regime to facilitate international dispute resolution. The contrasting views presented by the conventional perception of the homeward trend and the impartial rules of the Act present a significant puzzle for academics and lawyers alike advising clients doing business in China. Even assuming that there is a homeward trend, its exact degree of influence needs to be clarified. Not surprisingly, most courts around the world are said to favor the application of their laws in conflict disputes to some extent. For example, Ehrenzweig, who was a key figure of the lex fori school of modern conflict scholars, observes that “American courts have in fact nearly always given preference to their own laws in the decision of conflicts cases.” After all, judges are the experts on these laws and such expertise promotes timely and cost-efficient dispute resolution. Thus, a more precise question is probably not whether the label of homeward trend fits China, but the extent of such local favoritism. In order to answer this, the author decided to conduct this empirical review of the frequency with which Chinese courts apply Chinese law to conflict cases involving foreign-related contractual disputes. This would provide such necessary data to assess the extent of the homeward trend. However, the analysis should not stop there and must proceed to examine the reasons contributing to the homeward tendency.